Digestibility coefficients of sun dried and fermented aquatic macrophytes for Cachama blanca, Piaractus brachypomus (Cuvier, 1818) (Orinoquia, 2014)
The apparent digestibility coefficients of dry matter (ADCdrymatter), crude protein (ADCprotein) and the gross energy (ADCenergy) of the aquatic macrophytes Spirodela polyrhiza, Lemna minor and Azolla filiculoides treated by sun drying and lactic acid fermentation were determined for juveniles (31.0 ± 5.2 g) of Cachama blanca, Piaractus brachypomus. Each test ingredient was included at 300 g kg-1 in a semipurified reference diet containing chromium oxide as an indicator. Faeces were collected by a specific sedimentation system. The ADCdrymatter, ADCprotein and ADCenergy of the reference diet were 56.8%, 97.2% and 70.1%, respectively. The 3 x 2 factorial analysis of variances indicated that the digestibility coefficients of the tested macrophytes were significantly different between plant material and treatments, but not between their combinations. ADCprotein ranged from 74.9% to 84.5% in fermented macrophytes and from 51.1% to 60.4% in sundried macrophytes, indicating that the fermentation process had increased the protein digestibility of the aquatic plants (P
Keywords: Cachama; protein digestiblity; energy digestibility; fermentation